ANALISIS FRAMING PEMBERITAAN OTT BUPATI REJANG LEBONG DI RAKYAT BENGKULU ONLINE - Qhoir Adji Juanda Cipta; Eka Vuspa Sari; Kiemal Anugerah Saummy (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
This study aims to analyze the framing of news coverage regarding the Operation Catch-Hand (OTT) case involving the Regent of Rejang Lebong by the Corruption Eradication Commission (KPK) in Rakyat Bengkulu Online. This research employs Robert N. Entman’s framing theory, which consists of four elements: define problems, diagnose causes, make moral judgment, and treatment recommendation. The method used is a qualitative approach, with data collected through news documentation and in-depth interviews with media practitioners. The findings reveal that the framing of news coverage develops progressively following the dynamics of information, beginning with speculative reporting, shifting to more factual coverage after official confirmation, and ultimately emphasizing the designation of suspects and the disclosure of bribery practices in project procurement. These findings indicate that the media not only disseminate information but also actively construct reality by highlighting certain aspects in accordance with the evolution of information sources. Theoretically, this study demonstrates that framing in local media tends to be dynamic and aligned with the news production process, thereby contributing to the development of mass communication studies, particularly in understanding the construction of reality in corruption-related news coverage at the local level. Keywords: Framing, Online Media, OTT KPK, Reality Construction, Mass Communication